PERAN PERPUSTAKAAN PERGURUAN TINGGI DALAM MENDUKUNG IMPLEMENTASI SUSTAINABLE DEVELOPMENT GOALS 4 - Suprianingrum, Elvy; Heriyanto, Heriyanto (BACA: Jurnal Dokumentasi dan Informasi, 2021)
This study aims to identify the role of Academic libraries in supporting the implementation of Sustainable Development Goal 4. The research method employed was qualitative method using semi-structured interviews for data collection. The collected data then analyzed using Thematic Analysis, a qualitative data analysis for identifying pattern throughout the data. Two themes were emerged, that are Programs and Challenges. The Programs is a theme that explains the role the libraries to support the implementation of Sustainable Development Goal 4. It explains the providing access to information for users, the library cooperation programs with other parties who also take part in supporting the implementation of Sustainable Development Goal 4, and the training programs to develop human resources. The second, Challenges illustrate the activities or the policies in libraries which can hamper the libraries to support the implementation of Sustainable Development Goal 4. This research benefit university libraries in providing insights about how to support the implementation of Sustainable Development Goal 4.